PERANCANGAN SISTEM INFORMASI AKUNTANSI PENGAJUAN ANGGARAN BIAYA BERBASIS WEB DI KANTOR XXX - Fajrin Ramdani Fajrin Ramdani; Gunardi Gunardi; Yuda Syahidin yuda (EKBIS (Ekonomi & Bisnis), 2021)
This study aimed to determine the constraints, designing, and assist in the process of preparing the budget realization report using Microsoft Visual Basic.Net Programming language. The method used in this study of descriptive and qualitative methods development of the V-Model and engineering data collection through the method of observation and interviews. From the research finding some problem, including 1) The input data is still done manually by only using Microsoft Excel, so that the process of drafting the report realization of the less efficient 2) There are no special systems in the preparation of the report realization of the budget Therefore, the author of designing information system accounting the report realization of the budget programming Microsoft Visual Basic.Net by using the Microsoft Access. Contribution this research provided 1) With the information system accounting to the realization of the knowledge and training for the financial to run it. 2) information system that has been made by the authors of this to be used as materials for the development of the system further and can be developed at the network to facilitate in the preparation of the report realization of the budget. Keywords: Information System Accounting, The Realization Of The Budget, V-Model